An integrative health framework for wellbeing in the built environment. (November 2021) - Engineer, Altaf; Gualano, Ria J.; Crocker, Robert L.; Smith, Jacquelyn L.; Maizes, Victoria; Weil, Andrew; Sternberg, Esther M.
Abstract: This paper seeks to establish a framework for instantiating wellbeing in the built environment through the lens of integrative health. Integrative health is defined as "healing-oriented medicine that takes into account the whole person, including all aspects of lifestyle, " and includes seven core areas, or domains: sleep; resiliency; environment; movement; relationships; spirituality; nutrition. This framework can guide design professionals in including elements of the built environment to support each of these domains, and health professionals in understanding how elements of the built environment design can support integrative health. The goal of this review article is to connect these seven integrative health domains to built environment interventions that enhance and support healthy lifestyles and wellbeing. Common themes which emerge from the literature review include access to natural and circadian electrical lighting, views, connections to nature (biophilia), indoor air quality, control of one's environment, and spatial layout. There is a lack of research on how these domains of integrative health and built environment outcomes may be closely connected and influence each other. To address this need, we first discuss each of the seven domains and their connections to the built environment. We then provide suggestions on how to integrate these findings in design by discussing recently developed tools to promote health and wellbeing in the built environment: 1) the Sustainable Facilities Tool for healthy buildings developed by the US General Services Administration and its academic partners, and 2) other guidelines for healthy buildings. Highlights: An integrative health framework for wellbeing in the built environment. (74 char). Embedding integrative health's seven core areas into building design for wellbeing. (85 char). Reducing stress, enhancing resilience with built environment design and operation. (85 char). Enhancing physical and emotional health in built environments, beyond air quality. (84 char).